Dampak Implementasi International Financial Reporting Standards (IFRS) di Indonesia: Konvergensi Manajemen Laba dan Penghindaran Pajak - Franchika Kirana Bella; Vinisa Jaya Tri Wahyu Ghuna Khojanah; Aldisya Rachmadina; Desra Silvia; Ardyan Firdausi Mustoffa (Jurnal Akuntansi dan Pajak, 2023)
Financial statements information is an important aspect for users of financial statements. Investors want financial reports that are transparent and comparable to companies globally. The implementation of IFRS is an appropriate solution in determining the use of accounting standards globally, so it is hoped that the application of IFRS will have a good influence on the company. The purpose of this study is to examine the impact of the implementation of International Financial Reporting Standards (IFRS) in Indonesia. The methods used in this study are qualitative with a scoping review approach. The data used in this study is secondary data in the form of articles certified by the Science and Technology Index (SINTA) for the period 2018-2022. The results of this study conclude that most articles examining the impact of IFRS implementation on earnings management show that the implementation of IFRS will impact earnings management practices. Similar to tax avoidance, several related articles show that the adoption of IFRS has implications for tax avoidance.